2008
DOI: 10.1016/j.micpath.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid inhibits the infectivity and growth of Chlamydia pneumoniae in epithelial and endothelial cells through different receptors

Abstract: Chlamydia pneumoniae is a human respiratory pathogen that has also been associated with cardiovascular disease. C. pneumoniae infection accelerates atherosclerotic plaque development in hyperlipidemic animals and promotes oxidation of low density lipoprotein in vitro. All-trans-retinoic acid (ATRA), an anti-oxidant, has been shown to inhibit C. pneumoniae infectivity for endothelial cells by preventing binding of the organism to the M6P/IGF-2 receptor on the cell surface. This current study investigates whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…These findings are supported by in vitro experiments demonstrating that retinoic acid inhibits attachment of C. pneumoniae to host cells and intracellular growth and these actions are mediated through different receptors. As mentioned previously retinoic acid binds to the M6P/IGF-2 receptor and inhibits attachment and infectivity of C. pneumoniae in endothelial cells [6,7]. Similarly, other pathogens including herpes simplex virus [17] and varicella-zoster virus [18] have been reported to bind to M6P/IGF-2 receptors and the infectivity of these pathogens can be inhibited by ligands of the receptor.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These findings are supported by in vitro experiments demonstrating that retinoic acid inhibits attachment of C. pneumoniae to host cells and intracellular growth and these actions are mediated through different receptors. As mentioned previously retinoic acid binds to the M6P/IGF-2 receptor and inhibits attachment and infectivity of C. pneumoniae in endothelial cells [6,7]. Similarly, other pathogens including herpes simplex virus [17] and varicella-zoster virus [18] have been reported to bind to M6P/IGF-2 receptors and the infectivity of these pathogens can be inhibited by ligands of the receptor.…”
Section: Discussionmentioning
confidence: 93%
“…Cleavage of the glycan from the surface of C. pneumoniae organisms decreased infectivity of chlamydiae in cell culture [4] and mouse models of lung infection [5]. We further demonstrated that C. pneumoniae , but not C. trachomatis , binds to the mannose 6-phosphate/insulin-like growth factor-2 (M6P/IGF-2) receptor in endothelial cells, based on the finding that mannose 6-phosphate and retinoic acid, which bind to different sites on the receptor, inhibited attachment and infectivity of C. pneumoniae [6,7]. These findings suggest that the terminal mannose of the mannose oligosaccharide is phosphorylated [6].…”
Section: Introductionmentioning
confidence: 99%
“…Oligosaccharide, a kind of polymer consisting of 2–10 molecules of monosaccharide linked by glucosidic bonds, has attracted much attention because it not only is water-soluble, nontoxic, and biocompatible but also possesses versatile functional properties, such as antimicrobial, anticancer, antioxidant, and immunostimulant effects. Unfortunately, the disease resistance mechanisms of oligosaccharide in the plant system has remained unclear until now. Recent studies on the interaction between oligosaccharide and plant cells by fluorescence microscopy suggested that oligosaccharide could induce the plant cells to generate NO and H 2 O 2 , ,, which was involved in a diverse range of plant signal transduction processes and acted as a trigger signaling of plant responses against pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…The vitamin A derivative, retinoic acid, inhibits herpes simplex replication [ 301 , 302 ] as well as chlamydial infection and growth [ 303 ]. Vitamin A also stunts the growth of Helicobacter pylori [ 304 ].…”
Section: Resultsmentioning
confidence: 99%